(untitled) (Global Journal of Human-Social Science, 2021)
The main objective of this paper is to present an integrated model of university tutoring. The article is divided into two main sections: the first discusses a series of prior issues necessary to a full understanding of the current context of university tutoring (tutoring as a factor of quality in education, the strengths and weaknesses of the current tutoring model, the teaching function contrasted with that of tutoring); and in the second, the integrated model of tutoring is presented, exploring the rationale behind it, the characteristics defining it, its various objectives and dimensions, its intervention strategies and the organizational model best suited to its implementation.